Fundamental methods of mathematical economics - Chiang, Alpha C. (McGraw-Hill/Irwin, 2005)
It has been 20 years since the last edition of this classic text. Kevin Wainwright, a long time user of the text (British Columbia University and Simon Fraser University), has executed the perfect revision—-he has updated examples, applications and theory without changing the elegant, precise presentation style of Alpha Chiang. Readers will find the wait was worthwhile.